The shielding capacity of dental lead apron made from recycled x-ray lead foils - Mendenilla, Laarni D.; Lo, Katrina P.; Galban, Angelita (Adviser).
The study was done to assess the feasibility of recycling lead foils into lead aprons for dental purposes. It aims to evaluate in particular the shielding properties, durability, and the cost effectiveness of a recycled lead apron compared to a standard lead apron. Using an experimental research design, fluoroscopic and radiation tests were done to assess the integrity and lead equivalence of the control (standard lead apron manufactured by Proteqao Radiologica N Martins) and the experimental group (recycled lead apron made by researcher). Only one trial was done. An initial durability test by way of a high intensity light test was done on both groups prior to shielding and fluoroscopic tests. Results show that both groups exceed the recommended 0.25 lead equivalence. The standard lead apron had a lead equivalence of 0.37mm while the recycled lead apron had a 0.46mm lead equivalence. Fluoroscopic test showed presence of holes in both aprons. The standard lead apron had two tiny holes but is still acceptable for clinical use. The recycled lead apron had holes due to thread lines used to join the foils and is consequently unacceptable or clinical use. The recycles lead apron is also cost-effective since it is 100% cheaper than the standard lead apron and is likewise effective in shielding. Thus, the lead foils may be used for shielding purposes however the method of sewing is unacceptable since it creates holes where radiation may pass through.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Lead; Dental lead apron